Association Between Candidemia and Noninfectious Interstitial Pneumonia After Allogeneic Hematopoietic Cell Transplantation: JSTCT Transplant Complications Working Group. (27th March 2023) - Kimura, Shun-ichi; Akahoshi, Yu; Shiratori, Souichi; Okinaka, Keiji; Harada, Kaito; Uchida, Naoyuki; Doki, Noriko; Ikegame, Kazuhiro; Nakamae, Hirohisa; Tanaka, Masatsugu; Takada, Satoru; Kawakita, Toshiro; et al.
Abstract: Background: α-mannan from Candida albicans reportedly induces Th17-mediated pulmonary graft-versus-host disease (GVHD) in mouse models. This study aimed to evaluate the association between candidemia and noninfectious interstitial pneumonia (IP) in allogeneic hematopoietic cell transplantation (HCT) recipients. Methods: Using a Japanese transplant registry database, we analyzed 9143 pediatric and adult patients with hematological malignancies who underwent their first (n = 7531) or second (n = 1612) allogeneic HCT between 2009 and 2019. Results: Noninfectious IP was observed in 694 patients at a median (range) of 63 (0–1292) days after HCT. Candidemia occurred in 358 patients at a median (range) of 31 (0–903) days after HCT. Candidemia treated as a time-dependent covariate was significantly associated with an increased incidence of noninfectious IP (hazard ratio [HR], 2.51; 95% CI, 1.48–4.25), along with total body irradiation (>8 Gy; HR, 1.57; 95% CI, 1.18–2.10) and malignant lymphoma (vs acute myeloid leukemia; HR, 1.30; 95% CI, 1.004–1.69). On the other hand, prompt platelet recovery (HR, 0.58; 95% CI, 0.45–0.75) and acute lymphoblastic leukemia (vs acute myeloid leukemia; HR, 0.68; 95% CI, 0.49–0.94) were associated with reduced incidence of noninfectious IP. The median survival after the development of noninfectious IP in patients with prior candidemia was significantly shorter than that in those without it (22 days vs 59 days; P < .001). Conclusions: Candidemia was associated with an increased incidence of noninfectious IP. The prognosis of noninfectious IP after candidemia was extremely poor. Graphical Abstract: Graphical abstract